A new species of Proceratophrys Miranda-Ribeiro (Amphibia: Anura: Cycloramphidae) from the Chapada Diamantina, State of Bahia, northeastern Brazil - Napoli, Marcelo Felgueiras; Cruz, Carlos Alberto Gonçalves; de Abreu, Rafael Oliveira; Del-Grande, Maria Lucia (Zootaxa, 2011)
We describe a new species of Proceratophrys, allied to P. schirchi, from the northern sector of the Espinhaço mountain range, within a semiarid region in central State of Bahia known as Chapada Diamantina. The new species inhabits seasonal semi-deciduous forests (usually known as dry forests) that cover the mountainous relief of the Serra de Jacobina, a regional designation of the Espinhaço mountain range in northeastern Brazil. Proceratophrys minuta sp. nov. most resembles P. schirchi by combination of small palpebral appendages, general external morphology, and by its restriction to Atlantic Forest remnants. It is diagnosed from all congeners by the combination of small body size (snout–vent length, males 20.4–25.2 mm, females 28.3–31.9 mm), absence of rostral appendage, short palpebral appendages with the central prominent, dorsum adorned with sinuous longitudinal ridges outlining a spear-shaped ornamentation like a hastate-shaped leaf (with flaring pointed lobes at eyes and spear point at urostile), and other six morphological characteristics. We also describe the tadpole of P. minuta sp. nov., and compare its color and external morphology with other tadpoles of Proceratophrys described in the literature.